2020
DOI: 10.3389/fpsyg.2020.02231
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of the COVID-19 Epidemic on Guangdong College Students: The Difference Between Seeking and Not Seeking Psychological Help

Abstract: Background: Coronavirus disease 2019 (COVID-19) has considerably psychologically impacted Chinese college students. Several types of online mental health services were widely implemented for college students during the outbreak. This study investigated the relationship between college students' mental health status and psychological helpseeking behavior to test the phases-decision-making model (PDM). Methods: A cross-sectional survey was conducted among college students in Guangdong Province using an online pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 48 publications
8
62
2
3
Order By: Relevance
“…As a result of the increase in the time spend on social media, the students have become more exposed to read, heard, or see news related to the COVID-19 and therefore they were psychologically affected. Similar findings were previously mentioned in the studies conducting during the COVID-19 pandemic [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. It was reported that the students were experiencing psychological issues related to panic, depression, stress, anger, anxiety, sadness, fear confusion, as well as social dysfunction during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…As a result of the increase in the time spend on social media, the students have become more exposed to read, heard, or see news related to the COVID-19 and therefore they were psychologically affected. Similar findings were previously mentioned in the studies conducting during the COVID-19 pandemic [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. It was reported that the students were experiencing psychological issues related to panic, depression, stress, anger, anxiety, sadness, fear confusion, as well as social dysfunction during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…Supporting the health, mental health and well-being of all students should be of high priority in pandemic and post-pandemic times ( 63 ). Online programs, especially focusing on help-seeking behavior ( 64 ), chat interventions (e.g., with messenger services) and other low-threshold support programs or self-management interventions seem promising, easy to implement and are evidence-based for nearly all common mental health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure an equitable student experience in this new scenario, universities must guarantee that students from less privileged socioeconomic backgrounds are not disadvantaged. Students also found it difficult to maintain attention in a purely online context, reporting the following significant barriers (among others) (Liang et al, 2020 ; Mishra et al, 2020 ): boredom, sense of isolation, lack of time to follow the different subjects, and lack of self-organizing capabilities. Professors also noted that isolation was a significant problem in designing the courses, indicating the need to find the optimum balance of individual student-centered learning and collaborative learning, fostering virtual communities of practice to enhance student peer engagement and collaboration (Carolan et al, 2020 ).…”
Section: Transformation Of Higher Education To Face Covid-19 Disruptimentioning
confidence: 99%